The study of some structural parameters of the flora of chink Dongyztau (Aktobe region) - Kuanbay, Zh.I.; Abiyev, S.А.; Tikhomirov, V.N. (Fundamental and Experimental Biology, 2020)
The results of the study of structural indices of the flora of vascular plants chink Dongyaztau are presented in the article. According to the classification of life forms of I.G Serebryakov, the dominant share is occupied by perennial polycarpic herbs — 124 species, or 39.5 %, on the second position there are monocarpic herbs — 123 species, or 39.1 %. Semi-wood species make up 43 species, or 13.7 %, wood forms — 21 species, or 6.7 %. A high proportion of ephemera was noted which are 28 species, or 8.9 %. According to the classifica-tion of C. Raunkiaer in the flora chink Dongyztau is dominated by therophytes — 119 species, or 37.9 %. On the second place there is a group of hemi-cryptophytes — 104 species, or 33.1 %; in third place — chameophytes (46 species, or 14.6 %); in the fourth position — cryptophytes (31 species, or 9.9 %); on the fifth — phanerophytes (14 species, or 4.5 %). The ratio of life forms of plants according to both classifications confirms the climatic conditions of the region — sharp-continental and arid climate, timed to the desert zone of Kazakhstan. There are 10 useful groups of plants: fodder — 110 species; technical — 30 species; medicinal — 48 species; melliferous — 13 species; ornamental — 33 species; food — 33 species; vitamin — 11 species; poi-sonous — 32 species; insecticidal — 8 species; soil-, forest- and phytomeliorative — 11 species.